Analysis of Arabic Language Learning Methods at the Darul Hikmah Modern Islamic Boarding School in Medan - Siregar, Farida Khairani; Maisyara, Siti; Situmeang, Rusmin Nuryadin (Yayasan Rahmat Islamiyah, 2024)
This research aims to analyze Arabic language learning methods at the Darul Hikmah Modern Islamic Boarding School in Medan. In its implementation, researchers used a qualitative approach with descriptive analysis. The samples used were the Head of the Madrasah Tsanawiyah Modern Darul Hikmah Islamic Boarding School in Medan, Arabic language teachers and class VII students. Data collection carried out by researchers was in the form of observations, interviews, documentation taken when students were learning Arabic and carrying out triangulation to find the validity of the data obtained. The results of the research show that the method used by teachers at the Medan Darul Hikmah Modern Islamic Boarding School in learning Arabic is to use the reading method (Maharah Qira'ah) and the tarjamah method. With the Arabic language learning methods that have been implemented by the Darul Hikmah Modern Islamic Boarding School, Arabic language learning runs smoothly and students' ability to learn Arabic increases. The components contained in it are learning media and learning methods. With the efforts to improve Arabic language learning at the Darul Hikmah Medan Modern Islamic Boarding School, the application of Arabic language learning methods by teachers can improve students' Arabic language skills in everyday life in the Islamic boarding school environment and likewise students' ability to speak Arabic as well. more increasing.